Attitudes of the Working-Age towards Extending the Retirement Age - Vikraipat, Tawan; Srisatanon, Pornpana; Varoprakal, Sarapee; Panittumrong, Panida; Sangrod, Phutthachat (Rajapark Journal, 2026)
The purposes of this research were: (1) to study the level of attitudes toward extending the retirement age, (2) to compare attitudes toward extending the retirement age classified by personal factors, and (3) to study attitudes toward extending the retirement age and approaches to implementation. The research design utilizes a mixed-methods approach with a parallel database design. The sample consisted of 400 working-age individuals (15-59 years) in Bangkok and 12 interviewees. The research instruments were interview guides and questionnaires with a reliability coefficient of 0.927. The statistics used to analyze the data were percentages, means, and standard deviations, t-tests, and one-way ANOVA. The results of the research were as follows: (1) the attitudes toward extending the retirement age of working age in Bangkok were at a high level overall. (2) Working-age individuals with different occupations had significantly different attitudes toward extending the retirement age in terms of social factors at the .05 level. (3) Working-age individuals had more positive than negative attitudes toward extending the retirement age, with the forms of implementation of the retirement age extension concept being voluntary, only for positions or types of work that were necessary, and extending the retirement age in age ranges.